Home-based rehabilitation programs: Promising field to maximize function of patients with traumatic spinal cord injury - Rezaei, Mojtaba; Sharifi, Amirsina; Vaccaro, Alexander; Rahimi-Movaghar, Vafa (Asian Journal of Neurosurgery, 2019)
Background: Traumatic spinal cord injury (TSCI) has profound effects on the patient's health condition and function. However current treatment strategies fail in terms of cure. Thus, rehabilitative management has become the main gadget to promote patients' residual function. The most challenging aspect of rehabilitation is high costs of inpatient rehabilitation programs and poor continuity of care while patients are transferred to home. In this regard, numerous home based rehabilitation programs have been introduced. Objectives: This review is an attempt to better introduce and classify different aspects of home care programs for patients with TSCI all around the world. Methods: A literature search was conducted in the PubMed, Medline, and Google Scholar database. Studies that addressed rehabilitative programs for patients with TSCI in their home or home-like facilities were reviewed. Reference lists from retrieved articles were also reviewed. Results: Home based rehabilitation can be categorized in five different but naturally relevant fields: home aids/modification, home nursing and family help, social support, home based primary care (multidisciplinary physician groups), and novel models/methods (e.g. “transitional rehabilitation” or telemedicine). Conclusion: Since most investigators in TSCI home based rehabilitation have only introduced their findings, there are no comparative studies available. Thus future studies should be dedicated to clinical trials evaluating clinical efficacy of different strategies. A comprehensive integrated strategy with consideration to financial and other limitations should be applied to each specific area.
Keywords: Home care; rehabilitation; spinal cord injuries